Tailoring nitrogen fertilizer regimes to complement growth dynamics of diverse rice genotypes - Faisal; Lubis, I.; Junaedi, A.; Sopandie, D. (International Journal of Agricultural Technology, 2024)
Vegetative metrics and crop growth dynamics showed distinct trends amongst varieties IPB 3S exhibited early vigor in plant height, HIPA 21 showed prolific tillering while Mentik Wangi maintained conservative resource allocation across nitrogen levels. Yield component distribution and productivity diverged markedly; Hipa 21 achieved maximal grain weights per hill yet spikelet fertility constrained its yields below Inpari 33, which displayed enduring panicle formation and grain filling capacity translated into the highest yields overall. The results showed that the fertilizer at a dose of 90 kg ha-1 increased production yield and other production components. Concentrating availability during vegetative establishment and heading stages could show further potential productivity in initially vigorous types like Hipa 21 This research signified that accounting for genotypic growth traits and yield potentials is requisited to strategize nitrogen schemes for optimizing rice cultivar performance